Where the big fish eat the little fish : women's work in the free trade zones. - SAFA, Helen I. (1997)
Examines the conditions faced by workers at the free trade zones in the Dominican Republic. Points out that despite recently won gains in workers' rights, Dominican workers remain skeptical about the viability of organizing unions in the free-trade zones.